Paragraph shrinking as a strategy to improve reading comprehension - Zulfadli Abdul Aziz; Sofyan Abdul Gani; Zurina Zora (UPT Bahasa Universitas Tanjungpura, 2022)
This research was carried out to discover the effectiveness of using the paragraph shrinking strategy in improving students' reading comprehension, specifically in understanding general information, detailed information, reference, and vocabulary. The method of this was quasi-experimental design research. The population of this research was 224 students in the first grade of a junior high school. The results showed that students' average scores on general information increased from 410 in the pretest to 565 in the posttest. Likewise, their score of detailed information increased from 430 in the pretest became 605 in the posttest. Then, the students’ reference average score increased from 590 in the pretest become 610 in the posttest. Last, their vocabulary average score increased from 600 in the pretest to 630 in the posttest. Based on the results of the t-test, the df value was 29, and the deT value was 16.370. Based on the SPSS output of the table, the Sig. (2-tailed) had a p-value = 0.00, meaning that the p-value was <0.05. The researchers found that the null hypothesis (H0) was rejected. In conclusion, there is a significant improvement in students' reading comprehension after learning using the paragraph shrinking strategy.